2005
DOI: 10.1007/s00467-005-1894-9
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of peritoneal dialysis in children following cardiopulmonary bypass surgery

Abstract: Acute renal failure requiring renal replacement therapy can complicate cardiopulmonary bypass in children. Peritoneal dialysis has been shown to stabilize electrolytes and improve fluid status in these patients. To assess dialysis adequacy in this setting, we prospectively measured Kt/V and creatinine clearance in five patients (6-839 days of age) requiring renal replacement therapy at our institution. Median dialysis creatinine clearance was 74.25 L/week/1.73m(2) (range 28.28-96.63 L/week/1.73m(2)). Residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Fluid overload is a common complication following cardiac surgery in infants. Several treatments have been proposed to treat fluid overload in the context of cardiac failure and cardiac surgery including diuretics and peritoneal dialysis [15]. Most patients with heart failure who require diuretic therapy are treated with loop diuretics as they are powerful agents [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid overload is a common complication following cardiac surgery in infants. Several treatments have been proposed to treat fluid overload in the context of cardiac failure and cardiac surgery including diuretics and peritoneal dialysis [15]. Most patients with heart failure who require diuretic therapy are treated with loop diuretics as they are powerful agents [7].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management such as the use of diuretics is often insufficient to adequately manage fluid overload. Ultrafiltration through peritoneal dialysis or hemodialysis can be used in severe cases [4, 5], but may not be well tolerated. The insertion of a peritoneal drain and its use to remove peritoneal fluid postoperatively is commonly used in pediatric cardiac surgery especially when newborns with complex diseases are involved but data have never been published.…”
Section: Introductionmentioning
confidence: 99%
“…Les indications principales rapportées dans la littérature sont la déplétion hydrosodée en période postopératoire de chirurgie cardiaque et le traitement de l'IRA isolée. Plusieurs études confirment l'efficacité de la DP dans ces indications [120][121][122][123][124][125][126][127][128][129][130]. Les délais d'obtention d'une épuration efficace ne permettent pas d'utiliser la DP dans une indication urgente.…”
Section: Chez Les Patients Cérébrolésés à Risque D'hypertension Intraunclassified
“…More recently, CRRT was reported to be superior to PD in treating patients with malariainduced AKI (16), and this may have been due to the dosage of PD delivered, because the rate of creatinine clearance and correction of acidosis were much inferior during PD therapy; however, PD has been shown to be a clinically effective therapy in treating AKI, particularly in children after cardiac surgery. Very few studies have monitored the dosage of PD delivered to patients in AKI; one such study reported a weekly Kt/V urea in excess of 2.1, with a median creatinine clearance of 74.3 L/wk per 1.73 m 2 in children after cardiac surgery (17). Just as no studies have examined the optimum dosage of PD required for patients with single-organ and/or multiple-organ failure, there is a similar paucity of data on the recently introduced hybrid treatments (e.g., Genius, EDD, SLED).…”
Section: Dosage Of Rrtmentioning
confidence: 99%